2006
DOI: 10.1063/1.2204067
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the wall pressure trace downstream of a separated region using extended proper orthogonal decomposition

Abstract: Multipoint wall pressure measurements and Laser Doppler Velocimetry (LDV) measurements of the velocity field generated over a 30° forward facing ramp are discussed in this paper. Mean and fluctuating signals are analyzed both in the mean separated region and in the recovering boundary layer flow. We present an analysis based on proper orthogonal decomposition (POD). The choice of a “POD region” as a subset of the sensor array is discussed. In a “POD region” restricted to the mean separated region, we show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 15 publications
1
18
0
Order By: Relevance
“…Our observed distribution may be a consequence of such a distribution in the separated shear layer upstream of reattachment but the interaction with the wall has to be taken into account here. Hoarau et al (2006) have shown that the fluctuating pressure upstream of a reattachment is strongly correlated with that downstream of the reattachment. Therefore a simple convection of the vortices emanating from the separated shear layer could lead to such a distribution.…”
Section: Statistical Analysis Of Large Scale Vortices Evolution Aftermentioning
confidence: 97%
See 1 more Smart Citation
“…Our observed distribution may be a consequence of such a distribution in the separated shear layer upstream of reattachment but the interaction with the wall has to be taken into account here. Hoarau et al (2006) have shown that the fluctuating pressure upstream of a reattachment is strongly correlated with that downstream of the reattachment. Therefore a simple convection of the vortices emanating from the separated shear layer could lead to such a distribution.…”
Section: Statistical Analysis Of Large Scale Vortices Evolution Aftermentioning
confidence: 97%
“…Following the same reasoning, we clearly expect the coherence of the structure to decrease when moving downstream. Hoarau et al (2006) have conjectured that these structures, generated in the separated shear layer, lose their kinetic energy in one turn over time scale while being transported along the wall in the outer layer. These authors have proposed a simple model equation for the decrease of the coherent kinetic energy based on an equilibrium between advection and dissipation that can be easily solved for constant length scale and transport velocity.…”
Section: Statistical Analysis Of Large Scale Vortices Evolution Aftermentioning
confidence: 98%
“…In the central region, several authors suggested that the flow can be considered two dimensional ͑2D͒ at least in a statistical sense. In this regard, Hoarau et al 17 stated that the use of end plates to ensure a 2D flow is not feasible due to the induced disturbances but, without end plates, the flow is 2D in the central region. Other authors ͑e.g., Moss and Baker 18 and Kiya and Sasaki 5 ͒ confirmed this point and suggested a ratio larger than 10 between the spanwise extension of the step and its height in order to neglect the 3D effects in the central region.…”
Section: Experimental Setup and Flow Conditionsmentioning
confidence: 97%
“…Note that a long tube of 2 m length is connected to each sensor to adapt the impedance and to avoid acoustic resonances. For each probe, the frequency response is measured (magnitude and phase) with a B&K UA 0922 coupler and a reference microphone (see Hoarau et al, 2006 for more details). The signal/noise ratio of the pressure probe is 50 dB.…”
Section: Experimental Set-up and Measurements Techniquesmentioning
confidence: 99%